Possibility of oil seeds in feeding dairy cows - Süli, Ágnes; Béri, Béla; Csapó, János; Vargáné Visi, Éva (Acta Agraria Debreceniensis, 2014)
The efforts to modify the fatty acid composition of milk have intensified with health conscious nutrition coming to the forefront.This experiment of ours was designed to investigate to what extent the natural-based feed additives, such as oilseeds, can influence the fatty acid composition of cow’s milk.Further information was gained about feeding of oilseeds in specific amounts to be fitted into the technology of a large-scale dairy farm in practice. The feed supplements were whole, untreated rapeseed and whole, untreated linseed, as part of a total mixed ration. In case of saturated fatty acids when supplementing with whole rapeseed the most significant change was observable in the concentration of the caprylic acid, capric acid, undecylic acid, lauric acid, myristic acid, stearic acid. In case of unsaturated fatty acids the quantity of oleic acid enhanced considerably. When observating the feeding with whole linseed the concentration of many saturated fatty acids lowered (caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid). The quantity of some unsaturated fatty acids was showing a distinct rise after feeding with linseed, this way the oleic acid, α-linolenic acid, conjugated linoleic acid, eicosadienoic acid. The aim of the study was to produce food which meets the changed demands of customers, as well.